Faust - Goethe, Johann Wolfgang von; Wayne, Philip; Rouben Mamoulian Collection (Library of Congress) (Penguin, 1958)
Faust is the protagonist of a classic German legend. He is a scholar who is highly successful yet dissatisfied with his life, so he makes a pact with the Devil, exchanging his soul for unlimited knowledge and worldly pleasures. The Faust legend has been the basis for many literary, artistic, cinematic, and musical works that have reinterpreted it through the ages. Faust and the adjective Faustian imply a situation in which an ambitious person surrenders moral integrity in order to achieve power and success for a delimited term. The Faust of early books - as well as the ballads, dramas, movies, and puppet-plays which grew out of them - is irrevocably damned because he prefers human to divine knowledge; "he laid the Holy Scriptures behind the door and under the bench, refused to be called doctor of Theology, but preferred to be styled doctor of Medicine". Plays and comic puppet theatre loosely based on this legend were popular throughout Germany in the 16th century, often reducing Faust and Mephistopheles to figures of vulgar fun. The story was popularised in England by Christopher Marlowe, who gave it a classic treatment in his play, The Tragical History of Doctor Faustus. In Goethe's reworking of the story two hundred years later, Faust becomes a dissatisfied intellectual who yearns for "more than earthly meat and drink" in his life. - Amazon (summary for a later edition of this title).
Faust is the protagonist of a classic German legend. He is a scholar who is highly successful yet dissatisfied with his life, so he makes a pact with the Devil, exchanging his soul for unlimited knowledge and worldly pleasures. The Faust legend has been the basis for many literary, artistic, cinematic, and musical works that have reinterpreted it through the ages. Faust and the adjective Faustian imply a situation in which an ambitious person surrenders moral integrity in order to achieve power and success for a delimited term. The Faust of early books - as well as the ballads, dramas, movies, and puppet-plays which grew out of them - is irrevocably damned because he prefers human to divine knowledge; "he laid the Holy Scriptures behind the door and under the bench, refused to be called doctor of Theology, but preferred to be styled doctor of Medicine". Plays and comic puppet theatre loosely based on this legend were popular throughout Germany in the 16th century, often reducing Faust and Mephistopheles to figures of vulgar fun. The story was popularised in England by Christopher Marlowe, who gave it a classic treatment in his play, The Tragical History of Doctor Faustus. In Goethe's reworking of the story two hundred years later, Faust becomes a dissatisfied intellectual who yearns for "more than earthly meat and drink" in his life. - Amazon (summary for a later edition of this title).
Keywords: Devil. / fast / http://id.worldcat.org/fast/891974; German drama. / fast / http://id.worldcat.org/fast/941360; Devil / Drama.; German drama. / http://id.loc.gov/authorities/subjects/sh85054339; Drama. / fast / http://id.worldcat.org/fast/1423879